2014
DOI: 10.1002/ajhb.22512
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 2D:4D digit ratio and craniofacial shape in prepubertal children

Abstract: As several factors might be involved in the development and growth of both the craniofacial complex and fingers, the 2D:4D ratio, a putative proxy for fetal sex-hormone levels, is probably unable to impose a measurable effect within the variation of a normal population. Future research needs to examine an adult sample for potential covariation arising after the pubertal growth spurt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
0
1
Order By: Relevance
“…Given the methodological challenges of measuring the hormone environment in utero, human studies have typically relied upon 2D : 4D as an index of prenatal testosterone exposure. While several studies have reported a link between reduced 2D : 4D ratio ( purportedly reflecting exposure to increased levels of prenatal testosterone) and facial masculinity [31][32][33], there have been a number of notable failures to replicate these findings [45,46]. We have previously shown no association between testosterone levels in umbilical cord blood and adult 2D : 4D [21,22], and the current study found no within-sex link between 2D : 4D and the facial gender scores for either males or females.…”
Section: Discussioncontrasting
confidence: 62%
“…Given the methodological challenges of measuring the hormone environment in utero, human studies have typically relied upon 2D : 4D as an index of prenatal testosterone exposure. While several studies have reported a link between reduced 2D : 4D ratio ( purportedly reflecting exposure to increased levels of prenatal testosterone) and facial masculinity [31][32][33], there have been a number of notable failures to replicate these findings [45,46]. We have previously shown no association between testosterone levels in umbilical cord blood and adult 2D : 4D [21,22], and the current study found no within-sex link between 2D : 4D and the facial gender scores for either males or females.…”
Section: Discussioncontrasting
confidence: 62%